Realisme dalam Worldbuilding Melalui Studi Kasus pada Animasi Kimi no Na wa dan Song of the Sea - Hermanudin, Danika; Ahmad, Hafiz Aziz (Serat Rupa: Journal of Design, 2024)
Worldbuilding has become a center of attention in the entertainment industry, especially in animation. However, attention to worldbuilding studies is still lacking compared to character and narrative. Researchers argue that worldbuilding can be closely related to character creation, reflecting known human traits and characteristics. So that "emotional realism" is formed and empathy from the audience is created. Likewise, in worldbuilding, the audience needs to feel connected to elements that are known and real. Realism in animation aims to create an impression that is real or similar to the real world. This does not mean animation must perfectly mimic the real world but rather aims to make the audience feel a connection or attachment to what they are witnessing. In this research, there are two animations, Kimi no Na wa (2016) and Song of The Sea (2014), using two contrasting approaches but successfully building worlds by utilizing elements from real-world locations. Therefore, a descriptive comparative analysis is conducted to reveal the differences in approaches and focuses used by the animation creators in achieving realism in worldbuilding.